Treatment of borderline diabetes: controlled trial using carbohydrate restriction and phenformin. Issue 6091 (1st October 1977) - Jarrett, R J; Keen, H; Fuller, J H; McCartney, M
Abstract : A five-year therapeutic trial of carbohydrate restriction with or without phenformin (50 mg/day) was performed in men with borderline diabetes. The aim of treatment was to diminish the enhanced risk of cardiovascular disease and deterioration of glucose tolerance. Cardiovascular morbidity and mortality were not significantly affected by any form of treatment, alone or in combination. The predominant risk factor for cardiovascular morbidity and mortality and for overall mortality was the initial blood pressure level. The baseline plasma cholesterol concentration significantly predicted the onset of intermittent claudication. One implication of the results is that hypotensive treatment, supplemented when necessary with hypolipidaemic treatment, may be more effective in preventing the progression of arterial disease in people with mild to moderate glucose intolerance than conventional antidiabetic therapy.